Association of IL-4 and IL-10 Polymorphisms With Preterm Birth Susceptibility: A Systematic Review and Meta-Analysis - Cao, Xian-Ling; Zhou, Xuan-You; Xu, Nai-Xin; Chen, Song-Chang; Xu, Chen-Ming (Frontiers in Immunology, 2022)
Objective Preterm birth (PTB) is a typical inflammatory disease with unclear pathogenesis. The studies investigating the relationship between anti-inflammatory factors IL-4 and IL-10 gene polymorphisms and PTB produced conflicting results. This systematic review and meta-analysis aimed to summarize the effects of IL-4 and IL-10 gene polymorphisms and clarify their possible association with PTB. Methods A systematic literature review was conducted using PubMed, Web of Science, and Cochrane library (up to 02 April 2022). The MeSH terms, related entry terms, and other names in “Gene” database were used to find relevant articles. A fixed- or random-effects model was used to calculate the significance of IL-4 and IL-10 gene polymorphisms, depending on study heterogeneity. The odds ratios (OR) and 95% confidence intervals (CIs) were calculated in the allele, recessive, dominant, co-dominant, and over-dominant models. The Eggers publication bias plot was used to graphically represent the publication bias. Results Polymorphisms in two interleukins (IL-4-590C/T (rs2243250) = 5 and IL-10-592A/C (rs1800872), -819T/C (rs1800871) and -1082A/G (rs1800896) = 16) were found in 21 articles. Overall, only the over-dominant gene model AA + GG vs. AG revealed significant association between IL-10-1082A/G (rs1800896) and PTB (OR [95% CI] = 0.87 [0.76, 0.99], p = 0.04). However, in the allele model, recessive model, dominant model, co-dominant model, and over-dominant model, the polymorphisms for IL-4-590C/T (rs2243250), IL-10-592A/C (rs1800872), and IL-10-819T/C (rs1800871) were not found to be associated with the risk of PTB. In gene models, no statistically significant association was found between IL-4-590C/T (rs2243250), IL-10-592A/C (rs1800872), IL-10-819T/C (rs1800871), and IL-10-1082A/G (rs1800896) polymorphisms and PTB in subgroup analyses by racial or control group Hardy-Weinberg Equilibrium (HWE) p-value. Eggers’s publication bias plot and heterogeneity test (I2<50%, p = 0.05) of IL-10-1082A/G (rs1800896) suggested that the funnel asymmetry could be due to publication bias rather than heterogeneity. Conclusion The current study suggests that the over-dominant gene model AA + GG vs. AG of IL-10-1082A/G (rs1800896) polymorphism may be associated with genetic susceptibility to PTB and may have a protective function against PTB risk. There was unclear association found between IL-4-590C/T (rs2243250), IL-10-592A/C (rs1800872) and IL-10-819T/C (rs1800871) polymorphisms and PTB. Due to the limitations of included studies and the risk of publication bias, additional research is required to confirm our findings. Systematic Review Registration https://inplasy.com/inplasy-2022-4-0044, identifier INPLASY202240044.